Cleidocranial dysplasia: importance of radiographic images in diagnosis of the condition. - Tanaka, Jefferson L O; Ono, Evelise; Filho, Edmundo Médici; Castilho, Julio C M; Moraes, Luiz C; Moraes, Mari E L (Nihon University School of Dentistry, 2006)
Cleidocranial dysplasia (CCD) is a rare syndrome usually caused by an autosomal dominant gene, although 40% of cases of CCD appear spontaneously with no apparent genetic cause. This condition is characterized by several cranial malformations and underdevelopment, absence of the clavicles, and multiple supernumerary and impacted permanent teeth. The diagnosis of this condition is usually based on the presence of the main features (supernumerary teeth, partial or total absence of one or both the clavicles, and bony malformations) and on clinical and familial evidence. The bony and dental features of CCD may be visualized on radiographic images of the face and skull. Here, we present a familial case of CCD and discuss the importance of dental radiographs in diagnosis of the condition.
Keywords: adolescent; case report; child; cleidocranial dysplasia; cranial suture; female; human; jaw malformation; male; middle aged; panoramic radiography; radiography; tooth disease; tooth malformation; Adolescent; Child; Cleidocranial Dysplasia; Cranial Sutures; Female; Humans; Jaw Abnormalities; Male; Middle Aged; Radiography, Panoramic; Tooth, Impacted; Tooth, Supernumerary